Rab5 Isoforms Specifically Regulate Different Modes of Endocytosis in Leishmania - Rastogi, Ruchir (J Biol Chem, 2016)
Differential functions of Rab5 isoforms in endocytosis are not well characterized. Here, we cloned, expressed, and characterized Rab5a and Rab5b from Leishmania and found that both of them are localized in the early endosome. To understand the role of LdRab5 isoforms in different modes of endocytosis in Leishmania, we generated transgenic parasites overexpressing LdRab5a, LdRab5b, or their dominant-positive (LdRab5a:Q93L and LdRab5b:Q80L) or dominant-negative mutants (LdRab5a:N146I and LdRab5b:N133I). Using LdRab5a or its mutants overexpressing parasites, we found that LdRab5a specifically regulates the fluid-phase endocytosis of horseradish peroxidase and also specifically induced the transport of dextran-Texas Red to the lysosomes. In contrast, cells overexpressing LdRab5b or its mutants showed that LdRab5b explicitly controls receptor-mediated endocytosis of hemoglobin, and overexpression of LdRab5b:WT enhanced the transport of internalized Hb to the lysosomes in comparison with control cells. To unequivocally demonstrate the role of Rab5 isoforms in endocytosis in Leishmania, we tried to generate null-mutants of LdRab5a and LdRab5b parasites, but both were lethal indicating their essential functions in parasites. Therefore, we used heterozygous LdRab5a(+/−) and LdRab5b(+/−) cells. LdRab5a(+/−) Leishmania showed 50% inhibition of HRP uptake, but hemoglobin endocytosis was uninterrupted. In contrast, about 50% inhibition of Hb endocytosis was observed in LdRab5b(+/−) cells without any significant effect on HRP uptake. Finally, we tried to identify putative LdRab5a and LdRab5b effectors. We found that LdRab5b interacts with clathrin heavy chain and hemoglobin receptor. However, LdRab5a failed to interact with the clathrin heavy chain, and interaction with hemoglobin receptor was significantly less. Thus, our results showed that LdRab5a and LdRab5b differentially regulate fluid phase and receptor-mediated endocytosis in Leishmania.